PENGEMBANGAN KARIER BERDASARKAN IDENTITAS DAN ASPIRASI KARIER SANTRI (Pendampingan Bimbingan Karier di Pondok Pesantren Al-Kautsar Pamekasan) - Imam Hanafi; Ishlakhatus Sa’idah; Diana Vidya Fakhriyani (IAIN Madura, 2021)
Career planning is an essential aspect of individual career development. Skills in making career decisions are the main goals of career planning that every individual must take. Furthermore, career decisions taken by individuals cannot be separated from considerations of self-identity and social, which are a source of value and a place where various things are available individuals can use that for their development. In fact, not all individuals are capable of planning a career. Including the final year students at the Al-Kautsar Pamekasan Islamic Boarding School. The ability of the final year students to prepare for their careers is still low. This can be seen from the various problems that have arisen in relation to the choice of the type of further study, the choice of a job plan, and those related to the unpreparedness of high school graduates to enter further education. Therefore, it is necessary to make efforts to assist students in planning their future careers, one of which is through career guidance services packaged in Community Service. In the implementation of these activities, participants seemed enthusiastic about participating in activities that were marked by actively discussing career planning. The continuity of the implementation of this activity, namely ongoing assistance and consultation. (Perencanaan karier merupakan salah satu aspek yang penting dalam perkembangan karier individu. Kecakapan dalam mengambil keputusan karier merupakan tujuan utama dari perencanaan karier yang harus ditempuh oleh setiap individu. Selanjutnya, keputusan karier yang diambil individu tidak lepas dari pertimbangan identitas diri dan sosial yang merupakan sumber nilai dan tempat tersedianya berbagai hal yang dapat dimanfaatkan oleh individu bagi pengembangan dirinya. Faktanya, tidak semua individu mampu dalam merencanakan karier. Termasuk, pada santri tingkat akhir di Pondok Pesantren Al-Kautsar Pamekasan. Kemampuan santri tingkat akhir dalam mempersiapkan kariernya masih rendah. Hal ini tampak dari berbagai masalah yang muncul baik yang berkaitan dengan pemilihan jenis studi lanjutan, pemilihan rencana pekerjaan maupun yang berkaitan dengan ketidaksiapan para lulusan SMA dalam memasuki pendidikan lanjutan. Maka dari itu, perlu adanya upaya untuk membantu santri dalam merencanakan karier masa depannya, salah satunya yaitu melalui layanan bimbingan karier yang dikemas dalam Pengabdian Kepada Masyarakat. Dalam pelaksanaan kegiatan tersebut, peserta terlihat antusias mengikuti kegiatan yang ditandai dengan aktif berdiskusi tentang perencanaan kariernya. Keberlanjutan pelaksanaan kegiatan ini, yaitu dilakukan pendampingan dan konsultasi secara berkelanjutan).